Revisiting Macklin's arguments against the complete-lives principle - Abal, Federico German (2023)
In June 2020, Ruth Macklin published a critical essay against a guideline from the General HealthCouncil (Consejo de Salubridad General) of México that recommends using age as a tie-breaking criterion to allocate scarce therapeutic resources. The guideline bases this recommendation on the complete-lives principle. In this paper I reconstruct and reject the three arguments presented by Macklin against the complete-lives principle. Subsequently, I formulate three objections of my own to this principle.